2015
DOI: 10.1097/ppo.0000000000000118
|View full text |Cite
|
Sign up to set email alerts
|

Imaging the Tumor Microenvironment

Abstract: The tumor microenvironment is a complex, heterogeneous, and dominant component of solid tumors. Cancer imaging strategies of a subset of characteristics of the tumor microenvironment are under active development and currently used modalities and novel approaches are summarized here. Understanding the dynamic and evolving functions of the tumor microenvironment is critical to accurately inform imaging and clinical care of cancer. Novel insights into distinct roles of the tumor microenvironment in cancer progres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
42
0
3

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 63 publications
(45 citation statements)
references
References 41 publications
0
42
0
3
Order By: Relevance
“…LeBleu [11] To provide an overview of the different cell types and physiological parameters of the tumor microenvironment and how they affect tumor development…”
Section: Systematic Reviewmentioning
confidence: 99%
See 3 more Smart Citations
“…LeBleu [11] To provide an overview of the different cell types and physiological parameters of the tumor microenvironment and how they affect tumor development…”
Section: Systematic Reviewmentioning
confidence: 99%
“…An increasing number of studies have revealed that tumor-associated macrophages (TAMs) can augment, mediate, or antagonize the antitumor activity of irradiation, cytotoxic agents, and checkpoint inhibitors. The final cell type in the TME is the fibroblast [11,12,37]. Fibroblasts allow cancer cells to migrate from the primary tumor location into the bloodstream for systemic metastasis.…”
Section: The Tumor Microenvironmentmentioning
confidence: 99%
See 2 more Smart Citations
“…For example, determination of the best non-invasive imaging modality to use and protocol optimization for imaging the tumor microenvironment is actively being investigated and beginning to offer new insights [147]. An important area to address will be the development of methods to distinguish whether changes observed in the images of the tumor microenvironment following a liposome therapy are truly related to a response to the liposome therapy and not simply an artifact caused by perturbation of the microenvironment by the presence of the liposomes.…”
Section: Expert Opinionmentioning
confidence: 99%